COVID-19 and the pursuit of supply chain resilience: reactions and "lessons learned" from logistics service providers (LSPs). Issue 6 (15th June 2021) - Herold, David M.; Nowicka, Katarzyna; Pluta-Zaremba, Aneta; Kummer, Sebastian
Abstract : Purpose: The purpose of this paper is to provide new insights into the reactions and lessons learned with regard to the COVID-19 pandemic in terms of how logistics service providers (LSPs) managed to maintain supply chains resilience and what focus areas have been changed to keep operations functional and uphold financial stability. Design/methodology/approach: Based on data-gathering techniques in interpretive research this study collected primary data via semi-structured interviews, interviewing informants from selected LSPs that operate on a global scale. Findings: The results show that LSPs have built their reactions and actions to the COVID-19 outbreak around five main themes: "create revenue streams, " "enhance operational transport flexibility, " "enforce digitalization and data management, " "optimize logistics infrastructure" and "optimize personnel capacity." These pillars build the foundation to LSP resilience that enables supply chains to stay resilient during an external shock of high impact and low probability. Originality/value: The results of this study provide insights into how LSPs have managed the downsides and found innovative ways to overcome operational and financial challenges during the COVID-19 outbreak. As one of the first studies that specially focuses on the role of LSPs during the COVID-19 pandemic, this study categorizes the LSPs' reactions and provides a "lessons learned" framework from a managerial perspective. From a theoretical perspective, this paper discusses the strategic role of LSPs in supply chain management and thereby extends current supply chain literature with a focus on LSP resilience.